Clinical Implications and Impact of Discovery of the Thyroid Hormone Receptor on Integrin αvβ3–A Review - Hercbergs, Aleck (Frontiers in Endocrinology, 2019)
Hypothyroidism has been reported to improve survival in cancer patients but only recently has the putative mechanism been identified as a receptor for thyroxine and tri-iodothyronine on integrin αvβ3. Recognition of divergence of action of the pro-oncogenic L-thyroxine (T4) from pro-metabolic 3,5,3’-triiodo-L-thyronine (T3) has enabled clinical implementation whereby exogenous T3 may replace exogenous (or endogenous) T4 to maintain clinical euthyroid hypothyroxinemia that results in significantly better survival in advanced cancer patients without the morbidity of clinical hypothyroidism.